Association between operator volume and mortality in primary percutaneous coronary intervention - Daniel J Blackman; John P Greenwood; Paul D Baxter; Christopher J Malkin; Arvindra Krishnamurthy; Michelle Anderson; Kathryn Somers; Natalie Burton-Wood; Charlotte Harland; Jonathan M Blaxill; Stephen B Wheatcroft; Claire M Keeble; et al. (Open Heart, 2022)
Background There is a paucity of real-world data assessing the association of operator volumes and mortality specific to primary percutaneous coronary intervention (PPCI).Methods Demographic, clinical and outcome data for all patients undergoing PPCI in Leeds General Infirmary, UK, between 1 January 2009 and 31 December 2011, and 1 January 2013 and 31 December 2013, were obtained prospectively. Operator volumes were analysed according to annual operator PPCI volume (low volume: 1–54 PPCI per year; intermediate volume: 55–109 PPCI per year; high volume: ≥110 PPCI per year). Cox proportional hazards regression analyses were undertaken to investigate 30-day and 12-month all-cause mortality, adjusting for confounding factors.Results During this period, 4056 patients underwent PPCI, 3703 (91.3%) of whom were followed up for a minimum of 12 months. PPCI by low-volume operators was associated with significantly higher adjusted 30-day mortality (HR 1.48 (95% CI 1.05 to 2.08); p=0.02) compared with PPCI performed by high-volume operators, with no significant difference in adjusted 12-month mortality (HR 1.26 (95% CI 0.96 to 1.65); p=0.09). Comparisons between low-volume and intermediate-volume operators, and between intermediate and high-volume operators, showed no significant differences in 30-day and 12-month mortality.Conclusions Low operator volume is independently associated with higher probability of 30-day mortality compared with high operator volume, suggesting a volume–outcome relationship in PPCI at a threshold higher than current recommendations.